Improved Direct Torque Double Closed-Loop Control Algorithm for Induction Motor - Huaqiang ZHANG; Tong YAO; Shijun LUO (Institute of Advanced Engineering and Science, 2014)
This paper presents an improved direct torque control (DTC) algorithm as compared to a traditional DTC scheme. In the traditional scheme, a pair of hysteresis comparators is used to control motor stator flux and electromagnetic torque. This causes a variable switching frequency which results in a high flux and torque ripples. To mitigate these issues, an improved DTC algorithm based on a double closed-loop is presented. Acting the induction motor as a control object, a mathematical model of the flux and torque based on proportional and integral (PI) controller in the double closed-loop is established. With the flux and the torque treated as control variables, a smooth and continuous vector control and a fast-response DTC are observed. By adopting this improved DTC algorithm, the simulation and experimental results indicate that the flux and the torque ripples reduced greatly. Additionally, the static and dynamic performances of the system are improved because of the mentioned scheme operating at a constant switching frequency. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.4329